Improving T-cell assays for the diagnosis of latent TB infection: potential of a diagnostic test based on IP-10. - Morten Ruhwald (Public Library of Science (PLoS), 2008)
Background There is a need for simple tools such as the M.tuberculosis specific IFN-gamma release assays (IGRA) to improve diagnosis of M.tuberculosis-infection in children. The aim of the study was to evaluate the performance of an IP-10 and IL-2 based tests for the diagnosis of M.tuberculosis-infection in recently exposed children from Nigeria. Methodology and principal findings Samples were obtained from 59 children at high risk of infection with M.tuberculosis (contacts of adults with smear and culture-positive tuberculosis) and 61 at low risk (contacts of smear-negative/culture-positive tuberculosis or community controls). IP-10 and IL-2 was measured in plasma after stimulation of whole-blood with M.tuberculosis specific antigens and mitogen. Previously developed criteria for positive IP-10 and IL-2 tests were used and the diagnostic performances of the IP-10 and IL-2 tests were compared with the Quantiferon In-Tube (QFT-IT) and the Tuberculin Skin Tests (TST). In response to M.tuberculosis specific antigens, the high-risk children expressed significantly higher levels of IP-10 (1358 pg/ml[IQR 278-2535 pg/ml]) and IL-2 (164 pg/ml[11-590 pg/ml]) than low risk groups 149 pg/ml(25-497 pg/ml), and 0 pg/ml(0-3 pg/ml), respectively. There was excellent agreement (>89%,k>0.80) between IP-10, IL-2 tests and QFT-IT, better than with TST (>74%,k>0.49). The IP-10 and IL-2 responses were strongly associated with M.tuberculosis exposure and with grade of infectiousness of the index cases (p<0.0001). IP-10, IL-2, and TST but not QFT-IT was associated with age of the child in the low risk groups (p<0.02). Conclusions/significance IP-10 is expressed in high levels and results of the IP-10 test were comparable to the QFT-IT. IL-2 was released in low amounts in response to the antigens and not in response to the mitogen therefore IL-2 seems a less useful marker. We have demonstrated that IP-10 and possibly IL-2 could be alternative or adjunct markers to IFN-gamma in the diagnosis infection with M.tuberculosis.